Tackling Immune Targets for Breast Cancer: Beyond PD-1/PD-L1 Axis - Tabana, Yasser; Okoye, Isobel S.; Siraki, Arno; Elahi, Shokrollah; Barakat, Khaled H. (Frontiers in Oncology, 2021)
The burden of breast cancer is imposing a huge global problem. Drug discovery research and novel approaches to treat breast cancer have been carried out extensively over the last decades. Although immune checkpoint inhibitors are showing promising preclinical and clinical results intreating breast cancer, they are facing multiple limitations. From an immunological perspective, a recent report highlighted breast cancer as an "inflamed tumor" with an immunosuppressive microenvironment. Consequently, researchers have been focusing on identifying novel immunological targets that can tune up the tumor immune microenvironment. In this context, several novel non-classical immune targets have been targeted to determine their ability to uncouple immunoregulatory pathways at play in the tumour microenvironment. This article will highlight strategies designed to increase the immunogenicity of the breast tumour microenvironment. It also addresses the latest studies on targets which can enhance immune responses to breast cancer and discusses examples of preclinical and clinical trial landscapes that utilize these targets.